2001
DOI: 10.1016/s0002-9440(10)63061-1
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mutations in Nasal Natural Killer/T-Cell Lymphoma from Mexico

Abstract: Nasal NK/T-cell lymphoma is a unique form of lymphoma highly associated with Epstein-Barr virus, and with a characteristic geographic distribution. Recently, we showed that p53 is overexpressed in a high percentage of nasal NK/T-cell lymphomas. The aim of this study was to analyze the status of the p53 gene, and correlate it with the expression of p53 protein and its downstream target, the cyclin-dependent kinase inhibitor p21, in a series of 25 cases of well-characterized nasal NK/T-cell lymphoma from Mexico.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…We found a mutation in TP53 in one out of the five cases. Mutations in TP53 have been described in NKTCL at various proportions, suggesting some racial, environmental, or lifestyle differences as a possible cause of tumorigenesis, and appear to correlate with more advanced-stage disease [ 31 32 33 ]. In other lymphoma studies using NGS, including pediatric Burkitt lymphoma and mantle cell lymphoma, mutations in TP53 were also frequently found [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a mutation in TP53 in one out of the five cases. Mutations in TP53 have been described in NKTCL at various proportions, suggesting some racial, environmental, or lifestyle differences as a possible cause of tumorigenesis, and appear to correlate with more advanced-stage disease [ 31 32 33 ]. In other lymphoma studies using NGS, including pediatric Burkitt lymphoma and mantle cell lymphoma, mutations in TP53 were also frequently found [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note, loss of proteins such as FOXO3 and HACE1 may contribute to the apoptosis-resistance phenotype of EBV+ T/NK LPD by, respectively, preventing the induction of the pro-apoptotic BIM and PUMA, and by impairing TNF-driven NF-κB activation. Several recent studies have also identified activating mutations in STAT3 and STAT5B in up to 15% of ENKT lymphomas [ 142 , 143 ] and activating mutations in JAK have been variously observed [ 144 ]. Notably, all the STAT3 and STAT5B mutations were located in the SH2 domain, which is critical for STAT activation, and resulted in increased STAT phosphorylation, robust promotion of cell growth and cell survival under IL-2 limiting concentrations.…”
Section: Epstein–barr Virus-associated T/nk Cell Lymphoproliferative mentioning
confidence: 99%
“…For instance, genes located at 17p13.1 include those codifying for the aurora kinase B (AURKB), a centrosome-associated kinase that plays an important role as regulator of chromosome segregation and cytokinesis, and, for the tumor protein p53, a protein that causes cells with damaged DNA to arrest at the G1 phase of cell cycle (TP53). Deletions on TP53 , a tumor suppressor gene, are frequently found in neoplastic NK cells and have been associated with more advanced disease, suggesting a secondary oncogenic event rather than a triggering mechanism [ 38 ]. In addition, genes located at the 19q13 are the BAX and BCL3 apoptosis related genes [ 39 ], genes involved in cell cycle progression that codify for cyclins, such as CCNE1 , and genes codifying for transcription factors, such as FOSB [ 40 ], among others [ 41 ].…”
Section: Discussionmentioning
confidence: 99%